2015
DOI: 10.1097/iae.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Case-Matched Comparison of Vitrectomy, Peripheral Retinal Endolaser, and Endocyclophotocoagulation Versus Standard Care in Neovascular Glaucoma

Abstract: Endoscopic pars plana vitrectomy, panretinal photocoagulation, and ECP seem to control intraocular pressure to a greater extent than standard glaucoma treatments in patients with neovascular glaucoma. In this aged-matched comparative case series, there was no significant difference between the two treatments' effects on visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
4
25
2
Order By: Relevance
“…Marra et al reported a 70% reduction in IOP at postoperative month 12 in a cohort of patients only with neovascular glaucoma (NVG) . However, this NVG cohort had a mean preoperative IOP of 40.7 mmHg, significantly higher than our ECP‐plus cohort's mean preoperative IOP of 27.7 mmHg . Regarding medication reduction following ECP‐plus, we observed a modest effect compared to other studies; our cohort demonstrated a mean decrease of 2.1 medications, while other studies have reported a 2.7 to 2.8 reduction in mean number of medications following ECP‐plus .…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Marra et al reported a 70% reduction in IOP at postoperative month 12 in a cohort of patients only with neovascular glaucoma (NVG) . However, this NVG cohort had a mean preoperative IOP of 40.7 mmHg, significantly higher than our ECP‐plus cohort's mean preoperative IOP of 27.7 mmHg . Regarding medication reduction following ECP‐plus, we observed a modest effect compared to other studies; our cohort demonstrated a mean decrease of 2.1 medications, while other studies have reported a 2.7 to 2.8 reduction in mean number of medications following ECP‐plus .…”
Section: Discussioncontrasting
confidence: 85%
“…We noted an approximately 50% reduction in IOP from baseline at postoperative months 12 and 24, which is comparable to Tan et al's study reporting an approximately 65% IOP reduction at postoperative month 12 for patients with refractory glaucoma . Marra et al reported a 70% reduction in IOP at postoperative month 12 in a cohort of patients only with neovascular glaucoma (NVG) . However, this NVG cohort had a mean preoperative IOP of 40.7 mmHg, significantly higher than our ECP‐plus cohort's mean preoperative IOP of 27.7 mmHg .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations